Metabolic disorders in polycystic ovary syndrome: from gut microbiota biodiversity to clinical intervention - Li, Jiyuan; Qiao, Jiashen; Li, Yihan; Qin, Gaofeng; Xu, Yingjiang; Lao, Kaixue; Wang, Yanlin; Fan, Yang; Tang, Peiyi; Han, Lei (Frontiers in Endocrinology, 2025)
Polycystic ovary syndrome (PCOS) is a prevalent gynecologic endocrine disorder characterized by menstrual irregularities, elevated androgen levels, and ovulatory dysfunction. Its etiology is multifactorial. Emerging evidence indicates that PCOS patients exhibit diminished gut microbiota (GM) diversity and altered microbial ratios, contributing to the metabolic derangements observed in these individuals. This review elucidates the role of GM in the pathogenesis and metabolic disorders of PCOS, encompassing insulin resistance (IR), hormonal imbalances, bile acid metabolic disorders, Interleukin-22-mediated immune dysregulation, and brain-gut axis disturbances. Additionally, it synthesizes current therapeutic strategies targeting the GM, aiming to furnish a theoretical framework for prospective clinical interventions.